Copper Pairing in the Mordenite Framework as a Function of the CuI/CuII Speciation. (2nd November 2021) - Deplano, Gabriele; Martini, Andrea; Signorile, Matteo; Borfecchia, Elisa; Crocellà, Valentina; Svelle, Stian; Bordiga, Silvia
Abstract: A series of gas‐phase reactants is used to treat a Cu‐exchanged mordenite zeolite with the aim of studying the influence of the reaction environment on the formation of Cu pairs. The rearrangement of Cu ions to form multimeric sites as a function of their oxidation state was probed by X‐ray absorption spectroscopy (XAS) and also by applying advanced analysis through wavelet transform, a method able to specifically locate Cu–Cu interactions also in the presence of overlapping contributions from other scattering paths. The nature of the Cu‐oxo species formed upon oxidation was further crosschecked by DFT‐assisted fitting of the EXAFS data and by resonant Raman spectroscopy. Altogether, the Cu I /Cu II speciation clearly correlates with Cu proximity, with metal ion pairs quantitatively forming under an oxidative environment. Abstract : As evidenced by advanced X‐ray absorption spectroscopy analysis, Cu‐pairing in copper‐exchanged mordenite is favored by the +2 oxidation state. The optimal Cu–Cu distance in the oxidized state favors the formation of dimeric mono‐μ‐oxo dicopper sites.